Evaluation of Critical Resolved Shear Stresses for Various Plastic Deformation Mechanisms To Understand Mechanical Properties of Magnesium-Yttrium Alloys. Issue 1741 (27th February 2015) - Mineta, T.; Miura, S.
ABSTRACT: In order to understand enhanced mechanical properties of magnesium-yttrium (Mg-Y) alloys, applied stresses which were required to operate independent plastic deformation mechanisms on various stress axes were evaluated. Moreover, for this analysis, mechanical tests including newly-established testing method "pure-shear test" were conducted to evaluate Critical Resolved Shear Stresses (CRSSes) for various plastic deformation mechanisms of Mg-Y solid solution alloy single crystals with various Y concentration. Relatively higher solid solution strengthening of dominant plastic deformation mechanisms such as basal slip and extension twin at room temperature, results in increase in the activation of non-basal slip system. By a simple analysis based on von-Mises criterion with experimental CRSS values, it is revealed that enhanced mechanical properties of Mg-Y alloys might be attributed to the decrease of difference in the activity of plastic deformation mechanisms by Y addition.